2017
DOI: 10.3390/universe3010019
|View full text |Cite
|
Sign up to set email alerts
|

Janis–Newman Algorithm: Generating Rotating and NUT Charged Black Holes

Abstract: Abstract:In this review we present the most general form of the Janis-Newman algorithm. This extension allows generating configurations which contain all bosonic fields with spin less than or equal to two (real and complex scalar fields, gauge fields, metric field) and with five of the six parameters of the Plebański-Demiański metric (mass, electric charge, magnetic charge, NUT charge and angular momentum). Several examples are included to illustrate the algorithm. We also discuss the extension of the algorith… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
82
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(84 citation statements)
references
References 94 publications
(244 reference statements)
0
82
2
Order By: Relevance
“…, allows to solve the field equations for M (x), and transforming that solution back to g µν using that {q ab = g ab Ω + ; q mn = g mn Ω − }, where (a, b) contains the 2 × 2 block and (m, n) the maximally symmetric sector, one obtains the final solution for g µν as 154) with the definition z ≡ r/r c , where r…”
Section: Electromagnetic Fields In Higher Dimensionsmentioning
confidence: 99%
See 1 more Smart Citation
“…, allows to solve the field equations for M (x), and transforming that solution back to g µν using that {q ab = g ab Ω + ; q mn = g mn Ω − }, where (a, b) contains the 2 × 2 block and (m, n) the maximally symmetric sector, one obtains the final solution for g µν as 154) with the definition z ≡ r/r c , where r…”
Section: Electromagnetic Fields In Higher Dimensionsmentioning
confidence: 99%
“…To conclude, though many appealing results have been found in the context of Born-Infeld inspired modifications of gravity, there is plenty of room for further research in many different directions. 42 In this sense we point out that the applicability of the Janis-Newman method (which allows to obtain a rotating solution from a seed static metric, see Erbin for a review [154]) in the context of Born-Infeld inspired modifications of gravity is still to be understood. 43 Indeed, very recently it was found evidence on the existence of wormhole configurations above a certain mass threshold when a free static and spherically symmetric scalar field is let to gravitate under the BornInfeld dynamics [8].…”
Section: Final Remarksmentioning
confidence: 99%
“…This algorithm presents an alternative way for deriving rotating solutions by applying a particular complex transformation to a non-rotating static metric in four dimensions. More details may be found in [5]. To use this algorithm, we consider the usual form of a static metric in coordinate (t, r, θ, φ) as follows:…”
Section: Newman-janis Algorithmmentioning
confidence: 99%
“…This algorithm has been used to generate different rotating solutions. More explanations and detailed reviews can be found in [3][4][5][6][7][8][9][10]. In 1999, Kim was able to derive the AdS 3 rotating solution from the non-rotating one of Banados, Teitelboim, and Zanelli (BTZ) [11] by applying the Newman-Janis formulation.…”
Section: Introductionmentioning
confidence: 99%
“…The five-dimensional Myers-Perry (MP) black hole solution was obtained using simplification of the NJ algorithm proposed by Giampieri [6,7,8,9,10]. The authors in [10] also proposed a simpler NJ algorithm to generate five-dimensional rotating black holes.…”
Section: Introductionmentioning
confidence: 99%